PLEASE SOMEONE ANSWER I'VE ASK THIS QUESTION 4 TIMES AND NO ONE ANSWERS ME.
Things to do for #1-2:
A. Write an expression based on the given statement

b. Simplify the expression you just wrote
------
1. Find the sum of -7g and 4g + 2

2. Find the difference when 6ん is subtracted from 2ん - 4

Respuesta :

1. –3g + 2  

2. –4λ – 4

Step-by-step explanation:

1. Given data: –7g and 4g + 2

Now, let us find the sum of –7g and 4g + 2.

Sum of –7g and 4g + 2 = (–7g) + (4g + 2)

                                      = –7g + 4g + 2

                                      = –3g  + 2

2. Given data: 6λ and 2λ – 4

Now, let us find the difference when 6λ is subtracted from 2λ – 4.

6λ subtracted from (2λ – 4) = (2λ – 4) – 6λ

                                             = 2λ – 4 – 6λ

                                             = –4λ – 4

Hence the sum of –7g and 4g + 2 is –3g + 2 and the difference when 6λ  is subtracted from 2λ – 4 is –4λ – 4.